Microarchitecture is severely compromised but motor protein function is preserved in dystrophic mdx skeletal muscle - Friedrich, Oliver; Both, Martin; Weber, Cornelia; Schürmann, Sebastian; Teichmann, Martin D. H.; Wegner, Frederic von; Fink, Rainer; Vogel, M.; Chamberlain, J. S.; Garbe, Christoph S. (Biophysical journal, 2010)
Progressive force loss in Duchenne muscular dystrophy is characterized by degeneration/regeneration cycles and fibrosis. Disease progression may involve structural remodeling of muscle tissue. An effect on molecular motorprotein function may also be possible. We used second harmonic generation imaging to reveal vastly altered subcellular sarcomere microarchitecture in intact single dystrophic mdx muscle cells (∼1 year old). Myofibril tilting, twisting, and local axis deviations explain at least up to 20% of force drop during unsynchronized contractile activation as judged from cosine angle sums of myofibril orientations within mdx fibers. In contrast, in vitro motility assays showed unaltered sliding velocities of single mdx fiber myosin extracts. Closer quantification of the microarchitecture revealed that dystrophic fibers had significantly more Y-shaped sarcomere irregularities (“verniers”) than wild-type fibers (∼130/1000 μm3 vs. ∼36/1000 μm3). In transgenic mini-dystrophin-expressing fibers, ultrastructure was restored (∼38/1000 μm3 counts). We suggest that in aged dystrophic toe muscle, progressive force loss is reflected by a vastly deranged micromorphology that prevents a coordinated and aligned contraction. Second harmonic generation imaging may soon be available in routine clinical diagnostics, and in this work we provide valuable imaging tools to track and quantify ultrastructural worsening in Duchenne muscular dystrophy, and to judge the beneficial effects of possible drug or gene therapies.
Gesehen am 10.07.2023